2020
DOI: 10.1186/s12906-020-02942-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of neuroprotective and anti-amnesic effects of Elaeagnus umbellata Thunb. On scopolamine-induced memory impairment in mice

Abstract: Background Elaeagnus umbellata is abundantly found in Himalayan regions of Pakistan which is traditionally used to treat various health disorders. However, the experimental evidence supporting the anti-amnesic effect is limited. Therefore the study was aimed to evaluate the prospective beneficial effect of E. umbellata on learning and memory in mice. Objectives To assess neuroprotective and anti-amnesic effects of E. umbellata fruit extracts and is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 45 publications
4
37
0
2
Order By: Relevance
“…These compounds have already been described in other families, besides to Rosaceae with excellent anticholinesterase potential (Behl and Moosmann 2002;Hamaguchi et al 2009;Zafar et al 2019). The compound chlorogenic acid identified in the leaves sample has also been reported from other medicinal plants with significant neuroprotective effects and memory enhancing activities (Nazir et al 2020). These findings were further supported by their highest potential to inhibit both AChE and BChE.…”
Section: Discussionsupporting
confidence: 67%
“…These compounds have already been described in other families, besides to Rosaceae with excellent anticholinesterase potential (Behl and Moosmann 2002;Hamaguchi et al 2009;Zafar et al 2019). The compound chlorogenic acid identified in the leaves sample has also been reported from other medicinal plants with significant neuroprotective effects and memory enhancing activities (Nazir et al 2020). These findings were further supported by their highest potential to inhibit both AChE and BChE.…”
Section: Discussionsupporting
confidence: 67%
“…Both of them showed antioxidant activity in the brain as well as AChE inhibition. Nazir et al (2020) found out that E. umbellata fruit extract administered orally decreased the level of the highly active free radical, DPPH, in the hippocampus and frontal cortex. This antioxidant effect was associated with AChE inhibition and the procognitive effect in the novel object recognition test and Y-Maze test ( Nazir et al, 2020 ).…”
Section: Discussionmentioning
confidence: 98%
“… Nazir et al (2020) found out that E. umbellata fruit extract administered orally decreased the level of the highly active free radical, DPPH, in the hippocampus and frontal cortex. This antioxidant effect was associated with AChE inhibition and the procognitive effect in the novel object recognition test and Y-Maze test ( Nazir et al, 2020 ). The study of Roshanbakhsh et al (2020) revealed that another natural compound, piperine, improved memory impairments in rats by diminishing the iNOS level and increasing TAC in the hippocampus.…”
Section: Discussionmentioning
confidence: 98%
“…The plant is native to South Europe, Central Asia, Japan, China, India, Afghanistan, Azad Kashmir, and Himalayan areas of Pakistan [ 14 , 15 ]. Its berries fruit is a big source of antioxidant compounds (lycopene, β-carotene, lutein, phytofuluene, phytoene, β-cryptoxanthin, and α-cryptoxanthin), polyphenols, and vitamin E content (α-tocopherols and γ-tocopherols) with therapeutic significances [ 16 , 17 ]. Carotenoids and lycopene are the major sources for the astringent flavor of the berries fruits [ 18 ].…”
Section: Introductionmentioning
confidence: 99%